1998: ACSC ’98: Teaching communication skills in the disciplines: The Proceedings of the Australian Communication Skills Conference, The University of Melbourne October 1-2, 1998 - Tapper (Editor), Joanna; Gruber (Editor), Paul (Journal of Academic Language and Learning, 2026)
Formatting note: In the pdf, an article can be accessed directly by clicking on its title in the table of contents or via the Bookmarks pane. Foreword … v Contents … vi KEYNOTE ADDRESSES CAC Online: Enhancing Communication Across the Curriculum with information technology: Donna Reiss … 1 Lest we think the revolution is a revolution: Images of technology and the nature of change: Cynthia L. Selfe … 7 Electronic communication across the curriculum: Success breeds responsibility: Dickie Selfe … 20 Conceptualising CAC programs: Writing to Learn: Art Young … 25 Working toward an efficient and effective oral communication program at The College of William and Mary: Tamara L. Burk and Kirt E. Moody … 37 "The only native speaker in the room": Kate Chanock … 45 Giving international students a voice: Enabling participation in the culturally diverse classroom: Jeanne Dawson … 60 Can we talk?: The role of oral communication in student learning: Colleen Garside … 68 Cultural literacy and intercultural communication competence: Australia/ Asia and the Middle East: Harry Irwin … 78 Human and technological communication: An interactive world: Anita Jawary … 86 Students’ perceptions of teacher communication style in the use of pedagogies: A case study of expatriates teaching English in China: Ming-sheng Li … 94 Teaching communication in an engineering context-an experiment: Jane Madden … 106 Teaching postgraduate students how to get started and keep going with their theses: Emmanuel Manalo … 113 Genre, audience and thesis/ dissertation writing: Brian Paltridge … 122 "Do we really need to be here?": Meeting the needs of reluctant learners in communication skills classes: Ursula Pantelides … 136 The development of team/ group skills in an integrated business programme: Fleur Piper and Mary Thoreau … 145 Developing effective communication skills: Initiatives in commerce and economics: Prem Ramburuth … 151 Reflexive learning about communication and research: Exploring the benefits of participant-observation as an educative strategy: Anne Ring … 161 Developing analytical writing skills in applied science: Jan Robbins … 171 An evaluation of the use of simulated patients in teaching communication skills to pre-clinical medical students: Kathryn Robertson, Heather McCormack and Doris Young … 180 Contextualising communication skills in universities: Tony Schirato and Andrew Wallace …189 Teaching the fourth ’R’: Argument-a foundational communication skill: Paul Skrebels … 196 A major pedagogical challenge for traditionally trained students: Off with the security blanket and onto centre stage: Michael F. Tarttelin and Georgina M. Fyfe … 203 Writing at a tertiary level: Making the critical connections: Iris Vardi … 216 Joining forces: A combined faculty and learning support venture to improve the communication skills of commerce students: Glenis Wong-Toi … 228 WORKSHOPS Teaching modules for professional communication skills: Ric Caladine and Will Rifkin … 237 Small group teaching of communication skills in the health professions: Ken Jones and Marg Safron … 241 Casino Royale Canberra: Experiential Learning in Cross-Cultural communication using Jamieson’s simulation: Mary Kingsbury and Allan McLarin … 248 WORKS IN PROGRESS The challenge of tertiary literacy: Implementation of a multi-campus language and learning program: Rosemary Clerehan … 257 Notions of identity in cross-cultural communication: Snezana Dabic … 258 English for Specific Purposes-communicating understanding of content in first-year undergraduate units: Ann Dashwood … 259 Politicising pedagogy in business communication: Marianne Grey … 260 Enhancing student intercultural communication skills: Some practical strategies for instructors: Susan Hellmundt, Will Rifkin and Christine Fox … 261 Using simulation to develop communicative competence among non-native speakers of English: Virginia Hussin … 262 Stand and deliver! Message and person oriented discourse in explanation: Thao Le and Paul Throssell … 263 Ethnic and gender differences in communication skills of preclinical medicalstudents at the University of Melbourne: Heather McCormack and Doris Young … 264 Integrating the teaching and assessment of communication skills into a fourth-year mechanical engineering subject: Jane Moodie and Mir-Akbar Hessami … 265 Ideological tensions in constructivist-based communication skills writing programs: Issues of collaboration and assessment: Judith Morgan … 266 Video analysis in the teaching of communication skills to osteopathy students: Tony Morris and Peter Gibbons … 267 Collaboration within Internet-based project groups: A case study of the Research Writing Facility: David Tait, Clare Cahill, and Fiona Bavinton … 268 Communicating assignment expectations to undergraduates through varying task structures: Paul Throssell and Peter Ferguson … 269 Plagiarism as a communication issue in a culturally diverse academic setting: Richard Warner … 270 Teaching medical students about effective communication at the University of Melbourne: Doris Young … 271 POSTER PRESENTATIONS Developing oral and written communication skills in Science and Engineering: Jane Moodie and Mara Pavlidis … 275 Writing a lab report: Computer-based integration of academic literacy skills: Peter O’Carroll, Helen Drury and Janet Jones … 276 Developing and validating a learning skills matrix for first year students in agriculture and related courses: Carol Sheldrake, Mary J. Mahony and Janet Jones … 277